The quest for the ukrainian “Araucana”. The case for the humanization of the Orc - Lobo, Francisco (REVISTA ELECTRONICA IBEROAMERICANA, 2024)
The decade-long armed conflict between Russia and Ukraine (2014-2024) has been characterized legally and politically in different ways, such as a war of self-defense against external aggression to uphold the rules-based international order, or a war of national liberation against occupation and full-scale invasion by an imperialist power. On a social level, the rhetoric or language used by the immediately affected parties reveals the need to construct the conflict also as an existential fight between good and evil whereby the enemy is dehumanized by referring to them as “orcs.” Yet, this rhetoric could prove counter-productive as both a matter of principle and expediency. As a matter of principle, the same rules-based international order for which this just war of self-defense is being fought requires the humane treatment of the enemy. As a matter of expediency, the demeaning label “orc” risks being reclaimed by the enemy as a source of national pride and cultural identity, thus bolstering their will to fight and making a return to peace more difficult. The humanization of the enemy as both the right thing to do and the more convenient course of action is the best approach not only to win the war, but to fight and win well. The methodology used consists of textual analysis and philosophical argument drawing on primary and secondary sources. The former include historical works from both Hispanic and Ukrainian literature, namely the epic poem “La Araucana” (1569-1578-1590) by Alonso de Ercilla, and “Eneida” (1798) by Ivan Kotlyarevsky, a parody of the epic poem written by Virgil. Secondary sources include works of history, sociology, philosophy, law and ethics, as well as epic fantasy, namely J.R.R. Tolkien’s “The Lord of the Rings” and Kirill Eskov’s “The Last Ringbearer”.